Forever In Our Hearts: The births, deaths and marriages column in the Sydney Morning Herald, 1831–1860. Issue 2 (2nd April 2020) - Hess, Kristy; Pinto, Sarah
Abstract : This article charts the emergence of the births, deaths and marriages column in the colonial Australian press. Using Australia's oldest continuing newspaper the Sydney Morning Herald as a case study, this article examines the evolution of the notices over a 25-year period from the newspaper's first publication (as the Sydney Herald) in 1831. We argue that the births, deaths and marriages notices in the Herald were part of early attempts by colonists to reinforce their respectability before becoming a practice with widespread appeal that both announced key life events and marked people's connection to place. Drawing on the scholarship of Pierre Bourdieu, our analysis pinpoints the moment these notices were 'legitimised' by the journalistic field and marked the birth of a media ritual in colonial Australian society. We provide historical insight into the ways in which the news media establish legitimacy in the social spaces they serve.